Realistic Mathematics Education and Motivation in Elementary Mathematics Achievement - Imran Imran; Muhammad Khairul Wazni; Muhammad Halqi (IJE : Interdisciplinary Journal of Education, 2026)
Improving elementary students' mathematics achievement remains a persistent challenge, particularly in educational contexts where mathematics instruction is still dominated by procedural explanation and textbook-based practice. This study examined the effects of Realistic Mathematics Education (RME) and learning motivation on fifth-grade students' mathematics achievement and tested whether learning motivation moderated the effect of RME. A quasi-experimental non-equivalent control group design with a 2 × 2 factorial structure was employed. The participants were 40 fifth-grade students from two public elementary schools in Central Lombok Regency, Indonesia, assigned to an experimental group receiving RME-based instruction and a control group receiving conventional instruction. Data were collected using mathematics achievement tests, a learning motivation questionnaire, and classroom observation sheets. The instruments were validated by experts and demonstrated acceptable reliability. Data were analyzed using descriptive statistics, assumption testing, independent samples t-tests, two-way ANOVA, and effect size estimation. The findings showed that students taught through RME achieved significantly higher posttest scores than those taught through conventional instruction (M = 81.80 versus M = 70.00; p < .001), with a large practical effect (Cohen's d = 1.42). Learning motivation also had a significant main effect on mathematics achievement; however, the interaction between instructional model and learning motivation was not significant. These findings indicate that RME improves mathematics achievement across different motivational profiles. The study contributes to constructivist and motivational perspectives by showing that contextual pedagogy and learner motivation independently support elementary mathematics achievement. The results provide practical implications for designing contextual, student-centered mathematics instruction in developing educational contexts.